Effects of quercetin derivatives from mulberry leaves: Improved gene expression related hepatic lipid and glucose metabolism in short-term high-fat fed mice - Sun, Xufeng (Nutr Res Pract, 2015)
BACKGROUND/OBJECTIVES: Mulberry leaves contain quercetin derivatives, which have the effects of reducing obesity and improving lipid and glucose metabolism in mice with obesity. It is not clear whether or not mulberry leaves can directly affect metabolic disorders, in the presence of obesity, because of the interaction between obesity and metabolic disorders. The aim of the current study was to assess the direct action of quercetin derivatives on metabolic disorders in non-obese conditions in short-term high-fat diet fed mice. MATERIALS/METHODS: C57BL/6N mice were fed a high-fat diet, supplemented with either 0% (control), 1%, or 3% mulberry leaf powder (Mul) or 1% catechin powder for five days. Anthropometric parameters and blood biochemistry were determined, and hepatic gene expression associated with lipid and glucose metabolism was analyzed. RESULTS: Body and white fat weights did not differ among the four groups. Plasma triglycerides, total cholesterol, and free fatty acids in the 1%, 3% Mul and catechin groups did not differ significantly from those of the controls, however, plasma glucose and 8-isoprostane levels were significantly reduced. Liver gene expression of gp91phox, a main component of NADPH oxidase, was significantly down-regulated, and PPAR-α, related to β-oxidation, was significantly up-regulated. FAS and GPAT, involved in lipid metabolism, were significantly down-regulated, and Ehhadh was significantly up-regulated. Glucose-metabolism related genes, L-PK and G6Pase, were significantly down-regulated, while GK was significantly up-regulated in the two Mul groups compared to the control group. CONCLUSIONS: Our results suggest that the Mul quercetin derivatives can directly improve lipid and glucose metabolism by reducing oxidative stress and enhancing β-oxidation. The 1% Mul and 1% catechin groups had similar levels of polyphenol compound intake (0.4 × 10(-5) vs 0.4 × 10(-5) mole/5 days) and exhibited similar effects, but neither showed dose-dependent effects on lipid and glucose metabolism or oxidative stress.